Sustainable Forest Management in a Mediterranean region: Social preferences - Maroto Álvarez, C.; Segura, M.; Ginestar, C.; Uriol, J.; Segura, B. (Forest Systems, 2013)
Aim of study: There is a lack of empirical research that deals with sustainable forest management in Mediterranean regions, among the most vulnerable ecosystems. The main purpose of this work is to define the strategic criteria and objectives for sustainable forest management and aggregate the preferences of stakeholders in a Mediterranean region, using AHP and Goal Programming.Area of study: Valencian Community (Spain).Material and Methods: Firstly, we identified forest stakeholders and structured a decision hierarchy. Then a workshop was carried out to test and validate the proposed criteria and objectives, as well as a survey to determine social preferences. Secondly, another survey was conducted amongst experts to prioritize action plans.Main results: Stakeholders’ preferences gave the greatest importance to the environmental criteria (hydrological regulation and erosion, climate change mitigation and biodiversity) with an average weight of 40%.  Social criteria (employment, recreational activities and landscape) had a weight of 38% and 22% the economic criteria case (wood, hunting and fishing, livestock, renewable energies, rural tourism and mining). The results showed that new products and services such as tourism, renewable energies, landscape, hydrological regulation and erosion control, biodiversity or climate change mitigation are very relevant objectives. We also prioritized action plans comparing them with the distribution of the administration budget.Research highlights: The environmental and social criteria are much more important than the economic ones in the regional planning of the Mediterranean forest, regardless of the method used to aggregate the social preferences and if the forest is public or private.Key words: Multiple Criteria Decision Making; Goal Programming; Analytic Hierarchy Process; Preferences Aggregation.